Research of the development process of Khabarovsk in 1858–1966 - Tceluiko, Dmitry (project baikal, 2025)
The work is devoted to the analysis of the urban structure of Khabarovsk, how the districts were formed and how they are connected with each other. In the historical period under consideration (1858-1966) four urban development stages were identified: military outpost, industrial stage, Soviet and socialist stages. Each of the identified periods has a unique model of urban planning development: linear, regular, landscape and radial. The first large residential development was “GUPRovsky town”. The construction of the First microdistrict marked the beginning of planned development in Khabarovsk.
Keywords: Khabarovsk; architecture; urban development; history; district development; planning analysis